Effect of somatosensory amplification and trait anxiety on experimentally induced orthodontic pain. (26th February 2016) - Cioffi, Iacopo; Michelotti, Ambrosina; Perrotta, Stefania; Chiodini, Paolo; Ohrbach, Richard
Abstract : The perception of pain varies considerably across individuals and is affected by psychological traits. This study aimed to investigate the combined effects of somatosensory amplification and trait anxiety on orthodontic pain. Five‐hundred and five adults completed the State Trait Anxiety Inventory (STAI) and the Somatosensory Amplification Scale (SSAS). Individuals with combined STAI and SSAS scores below the 20th percentile (LASA group: five men and 12 women; mean age ± SD = 22.4 ± 1.3 yr) or above the 80th percentile (HASA group: 13 men and seven women; mean age ± SD = 23.7 ± 1.0 yr) were selected and filled in the Oral Behaviors Checklist (OBC). Orthodontic separators were placed for 5 d in order to induce experimental pain. Visual analog scales (VAS) were administered to collect ratings for occlusal discomfort, pain, and perceived stress. Pressure pain thresholds (PPT) were measured. A mixed regression model was used to evaluate pain and discomfort ratings over the 5‐d duration of the study. At baseline, the LASA group had statistically significantly higher PPT values for the masseter muscle than did the HASA group. During the experimental procedure, the HASA group had statistically significantly higher discomfort and pain. A significant difference in pain ratings during the 5 d of the study was found for subjects in the HASA group. Higher OBC values were statistically significantly positively associated with pain. Somatosensory amplification and trait anxiety substantially affect experimentally induced orthodontic pain.